Analyzing and examining the supernatural connection between human actions and environmental phenomena (with emphasis on Ayatollah Javadi Amoli's point of view) - Ali Ghadrdan Ghramaleki; Mohammad Hasan Ghadrdan Gharamaleki (حکمت اسرا)
Some of the religious texts have informed about the relationship between some human actions and environmental phenomena, which cannot be explained in a normal way and with natural and experimental knowledge. Considering the principle of causality and religion's emphasis on rationality, it is necessary and necessary to examine the relationship between human actions and environmental effects and the quality of the effects of these actions, so the purpose of this research is to explain the reasonableness of the relationship between some human actions and the environment. In appearance and in a normal and natural way, they are considered unrelated. In order to achieve this goal, in this research, the author of the problem has collected the information needed for the research with library research and explained and analyzed the problem and its sub-sections with rational and narrative, comparative and critical analysis. In this research, emphasizing the view of Ayatollah Javadi Amoli, it was clarified that human actions, in addition to normal and normal effects, are also possible in supernatural and abnormal ways in the world of nature, and this effect has also been realized. The inner form of human actions, single soul and divine will are among the spiritual and supernatural causes and factors that affect the environment after human actions and cause the emergence of natural environmental effects.